PENERAPAN MODEL PEMBELAJARAN CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA SOAL CERITA SISWA KELAS VIII A MTS GUPPI MEKKATTA DALAM PEMBELAJARAN MATEMATIKA - Anwar, Makmur; Muliana, Ana; Murtafiah (PEDAMATH: Journal on Pedagogical Mathematics, 2025)
The purpose of this study was to improve students' problem-solving abilities in mathematical story problems by using the CIRC learning model in class VIII A students of MTs Guppi Mekkatta in the 2023/2024 academic year, with the material of Relations and Functions and Straight Line Equations. The population in this study were all students of class VIII A MTs GUPPI Mekkatta. With this research design using a modification of the Kemmis and McTaggart model in 2 cycles consisting of planning, implementation, observation, and reflection. Data collection techniques used tests, questionnaires, observation and documentation. The research instrument used problem-solving ability test questions, questionnaires and observation sheets. Data analysis techniques were carried out descriptively quantitatively and descriptively qualitatively. The results of the study showed that the results of students' problem-solving ability tests in cycle I had an average score of 57 and the percentage of learning completeness was 20% with a very low category. Furthermore, in cycle II the average value of students became 81 and the percentage of student learning completion became 80% with a good category then for student responses can be seen in cycle I with a less positive category with an average value percentage of 69% then in cycle II the results of the student response questionnaire increased, where the average value obtained was 91% with very positive criteria. With this it can be stated that the success indicator has been achieved in cycle II.